Impact of the COVID-19 Pandemic on Inpatient Antibiotic Consumption in Switzerland - Olivier Friedli; Michael Gasser; Alexia Cusini; Rosamaria Fulchini; Danielle Vuichard-Gysin; Roswitha Halder Tobler; Nasstasja Wassilew; Catherine Plüss-Suard; Andreas Kronenberg (MDPI AG, 2022)
The aim of this study was to analyze inpatient antibiotic consumption during the first 16 months of the COVID-19 pandemic in Switzerland. The entire period (January 2018-June 2021) was divided into the prepandemic period, the first and second waves, and the intermediate period. In the first year of the pandemic, total overall inpatient antibiotic consumption measured in defined daily doses (DDD) per 100 bed-days remained stable (+1.7%), with a slight increase in ICUs of +4.2%. The increase in consumption of broad-spectrum antibiotics was +12.3% overall and 17.3% in ICUs. The segmented regression model of monthly data revealed an increase in overall antibiotic consumption during the first wave but not during the second wave. In the correlation analysis performed in a subset of the data, a significant positive association was found between broad-spectrum antibiotic consumption and an increasing number of hospitalized COVID-19 patients (p = 0.018). Restricting this dataset to ICUs, we found significant positive correlations between the number of hospitalized COVID-19 patients and total antibiotic consumption (p = 0.007) and broad-spectrum antibiotic consumption (p < 0.001). In conclusion, inpatient antibiotic use during the different periods of the COVID-19 pandemic varied greatly and was predominantly notable for broad-spectrum antibiotics.